Pelatihan Literasi Keuangan untuk Gen Z di SMK - Sumardi Sumardi; Pahman Habibi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
High school/ vocational high school students are the target of increasing financial literacy due to the large number of financial and educational institutions that provide insight into financial literacy to the public. This will be related to the Financial Services Authority (OJK) report in 2019 which conducted a survey on financial literacy and inclusion, the results of which showed that the financial literacy index of the Indonesia people increased from 29,7% in 2016 to 38,03% while the financial inclusion indexincreased from 67,8% to 76,19%. SMA/ SMK students are directed to be able to understand financial literacy. Although there are still many high school/ vocantional students who are not good at financial literacy which cause students to be less able to control themselves so they tend to behave consumptively. Therefore, to support the goverment in increasing the financial literacy index, financial literacy training was held for students of SMK Bina Informatika located in South Tangerang. This training will introduce students to various types of investment instruments and how to start a business at a young age. So that students are able to manage their finances and are excited to build a business. Keywords: financial literacy, investment, business